Snow Compaction - Investigation of Metamorphism of Snow - Stehle, N. S. (1970)
Although processing and compacting increase the density and bearing capacity of surface snow for use as roads and trails, these processes have not been able to achieve the degree of densification that occurs naturally as snow slowly metamorphoses to glacier ice. A study was made at the Naval Civil Engineering Laboratory of the processes and influences of the major mechanisms that control snow metamorphism--grain size, pressure, temperature and solar radiation--in order to provide a basis for developing better techniques for higher strength snow pavements. It was concluded that maximum snow strengths are achieved at or near a critical density of 60 gm/cu cm, followed by bond growth, or age hardening, at temperatures between -12C and -7C. In addition, as distribution of applied loads with depth is essential to the development of operational criteria for such pavements, it is recommended that research be conducted to develop this knowledge.